2012
DOI: 10.1111/j.1751-228x.2011.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Verbal Working Memory Depends on Vocabulary: Oral Reading Fluency in Adolescents With Dyslexia

Abstract: Most research on dyslexia to date has focused on early childhood, while comparatively little is known about the nature of dyslexia in adolescence. The current study had two objectives. The first was to investigate the relative contributions of several cognitive and linguistic factors to connected‐text oral reading fluency in a sample of adolescents with dyslexia (n = 77). The second was to test the hypothesis that the effect of verbal working memory on connected‐text oral reading fluency is moderated by word‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 52 publications
(67 reference statements)
6
18
1
2
Order By: Relevance
“…Adults with dyslexia have been reported to experience (working) memory problems [4], attentional deficits [5], reduced processing speed [2], problems with fast word finding and arithmetic [6][7], and less elaborated vocabulary skills [8]. Dyslexia has also been associated with less sophisticated study strategies and metacognitive skills [9]–[10], higher anxiety, lower self-esteem, problems with coping, and deficient academic achievement and motivation throughout the life-span [11][13].…”
Section: Introductionmentioning
confidence: 99%
“…Adults with dyslexia have been reported to experience (working) memory problems [4], attentional deficits [5], reduced processing speed [2], problems with fast word finding and arithmetic [6][7], and less elaborated vocabulary skills [8]. Dyslexia has also been associated with less sophisticated study strategies and metacognitive skills [9]–[10], higher anxiety, lower self-esteem, problems with coping, and deficient academic achievement and motivation throughout the life-span [11][13].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have similarly found that children with RD can rely on morphological structure to decode words faster, despite decoding difficulties [38,39]. Vocabulary skills have also been implicated as a compensatory mechanism for college students with RD [40], and have been shown to mediate between impaired verbal working memory and oral reading fluency in adolescents with RD [41]. More superior verbal reasoning skills in general have been shown to explain higher reading, spelling, morphological, and syntactic skills in students with RD [42].…”
Section: Cognitive Resiliencementioning
confidence: 99%
“…Poor reading comprehension in high school students may result from weak decoding, vocabulary, and/or listening comprehension skills (Braze, Tabor, Shankweiler, & Mencl, 2007). Deficits in vocabulary and working memory that underlie childhood dyslexia may still be present in adolescents with SLDs, but word level skills may become a weaker predictor (Rose & Rouhani, 2012). …”
Section: Specific Research Aim and Four Research Questionsmentioning
confidence: 99%